Ramesses II, Egypt's ultimate Pharaoh - Brand, Peter J. 1967- (Lockwood Press, 2023)
Warrior, mighty builder and statesman, over the course of his 67-year-long reign (1279-1212 BCE), Ramesses II achieved more than any other pharaoh in the three millennia of ancient Egyptian civilization. Drawing on the latest research, Peter Brand reveals Ramesses the Great as a gifted politician, canny elder statesman, and tenacious warrior. With restless energy, he fully restored the office of Pharaoh to unquestioned levels of prestige and authority, thereby bringing stability to Egypt. He ended almost seven decades of warfare between Egypt and the Hittite Empire by signing the earliest international peace treaty in recorded history. In his later years, even as he outlived many of his own children and grandchildren, Ramesses II became a living god and finally, an immortal legend. Brand paints with authoritative knowledge and colourful details a compelling portrait of this legendary Pharaoh who ruled over Imperial Egypt during its Golden Age
Keywords: Ramses -- II. -- Ägypten, Pharao -- v1290-v1223; Biografie